2013
DOI: 10.2355/isijinternational.53.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxidation State of Iron Ions on the Viscosity of Alkali Silicate Melts

Abstract: Understanding the changes in viscosity due to the different oxidation states of iron ions is important for simulating phenomena related to molten slags and also for understanding the structure of iron-oxidecontaining silicate melts. However, these viscosity changes are not well understood. Here, we show the viscosity changes of R2O-SiO2-FexO (R = Li, Na, or K) melts due to changes in the oxidation states of the iron ions by systematically varying the oxygen partial pressure using several Ar-based gases at 1 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…18) In order to make the value of Fe 3 + /Fe 2 + within this range, a suitable oxygen partial pressure must be taken into account. Based on previous study, 20) it is found that when the value of Fe 3 + /Fe 2 + was between 0.13 and 0.16 at 1 773 K in the R-Si-Fe-O system (R = K or Na), oxygen partial pressure was approximately 10 − 10 atm. The Ca-Si-Fe-O system in this study is similar to the above system, so the oxygen partial pressure in our experiment can be designed in terms of R-Si-Fe-O system.…”
Section: Slag Composition Designmentioning
confidence: 88%
See 1 more Smart Citation
“…18) In order to make the value of Fe 3 + /Fe 2 + within this range, a suitable oxygen partial pressure must be taken into account. Based on previous study, 20) it is found that when the value of Fe 3 + /Fe 2 + was between 0.13 and 0.16 at 1 773 K in the R-Si-Fe-O system (R = K or Na), oxygen partial pressure was approximately 10 − 10 atm. The Ca-Si-Fe-O system in this study is similar to the above system, so the oxygen partial pressure in our experiment can be designed in terms of R-Si-Fe-O system.…”
Section: Slag Composition Designmentioning
confidence: 88%
“…The researches indicated that the iron redox state was as a function of pressure, temperature and bulk composition. 13,20) Under the same condition of other factors, the Fe 3+ / Fe 2+ ratio decreased with increasing ionic potential (Z/r) of non-framework cations and had positive correlation with oxygen partial pressure. 13,18) The Z/r of K + , Na + and Ca 2+ is 0.75, 1.02, 2.00, respectively.…”
Section: Slag Composition Designmentioning
confidence: 96%
“…This process is related with the structural relaxation ( α relaxation) seen in the glass‐formation process. [ 1–3,27,28 ] In the supercooled liquid state below T m , the viscous flow occurs due to breaking and switching the bonds connecting the structural units (or molecular units). Likewise, bond twisting can also trigger the flow of adjacent structural units.…”
Section: Ac Phenomena In the Structural Relaxation And The Electricalmentioning
confidence: 99%
“…Stage three involves the crystallization of the DS and the solidification with a silicate glassy phase from this homogeneous melt. Osugi et al [25] reported that the oxidation state of iron ions, and the coordination structure of Fe 3+ had a great influence on the viscosity of the melt. Fe 3+ plays an intermediate role between the network former and the network modifier since it forms both tetrahedra [FeO 4 ] and octahedra [FeO 6 ].…”
Section: Discussionmentioning
confidence: 99%